Students’ Responses to Guided Discovery Based-Worksheets in Physics Material on the Respiratory System - Desy Purwasih; Jumadi Jumadi (Journal of Mathematics Science and Computer Education, 2021)
This study aims to determine students' response in junior high school to the development of guided discovery-based worksheets. The type of the research is Research and Development (R&D). The sample used was 28 students of class VIII in Junior High School using purposive sampling. The data was collected by providing a previously validated student response questionnaire. Based on the results of data analysis, the average student response for each aspect in a row is 90.2%; 86.8%; 87.9%, with an average overall response of 88.3% with a very good category. The conclusion from this research, the worksheets can be used in learning, marked by the very good response of students to the developed guided discovery-based worksheets.